Da democracia à ciberdemocracia: condições e (in)efetividade da participação popular na construção colaborativa do marco civil da internet - Rodegheri, Leticia Bodanese (2015)
Representative democracy is undergoing a period of transformation, because while it is the political system of government adopted in most countries, has been the subject of much critique. There is a perception of a gap between citizens and representatives, deviations of public funds and corruption, situations that refer to the six broken promises of democracy brought by Norberto Bobbio. In order to change this scenario, the Information and Communication Technologies (ICT), particularly the Internet, appear as a new element that can attract public participation around government affairs. This is the construction of cyberdemocracy that, however, shares opinions of authors and researchers of the transformer potential of internet. In this scenario, there is the e-Democracy Website, linked to the Chamber of Deputies, that incites the popular participation to contribute in the forums, chats and wikilegis with the law projects pending in the Legislature or to suggest new projects. This research aims to analyze the manifestations of a specific Community Legislative of this Portal related to the Civil Rights Framework for the Internet in order to address an overview of popular participation in law projects online in Brazil. The research problem concerns the conditions for mass demonstrations on the internet and the effectiveness of such propositions, to check whether they are obeyed and considered by deputies when the deliberation of the projects in plenary. It is employed the hypothetical-deductive method of approach, formulating two main hypotheses. The first is the sense that the use of the internet is the most appropriate way to strengthen representative democracy. The second refers to the digital divide as the greatest obstacle to that popular online participation. Among the variables, there are the access rates to computers and the internet, public interest in accessing government portals and if the popular participation in the Portal is effectively considered by deputies. Are used the monographic and comparative methods of procedure and, as a research technique are used direct, systematic and non-participant observation of e-Democracy Website and Digital Culture blog, considering that the construction of the draft bill of the Civil Rights Framework for the Internet also occurred collaboratively. The conclusion is that the scenery around the popular online participation in law projects is still in the beginning, with a minority of the demonstrations was considered in the adoption of law projects, showing that the spaces have as main feature the spread of the subject and the promotion of debates among citizens themselves.